Shengu granules ameliorate ovariectomy-induced osteoporosis by the gut-bone-immune axis - Chen, Xiao cong; Li, Wei ju; Zeng, Jia ying; Dong, Yun peng; Qiu, Jian ming; Zhang, Bing; Wang, Dong yang; Liu, Jun; Lyu, Zhao hui (Frontiers in Microbiology, 2024)
Postmenopausal osteoporosis (PMOP) is a common chronic disease, and the loss of bone density and bone strength after menopause is its main symptom. Effective treatments for PMOP are still uncertain, but Chinese medicine has some advantages in slowing down bone loss. Shengu granules are often used clinically to treat PMOP. It has been shown to be an effective prescription for the treatment of PMOP, and there is evidence that gut flora may play an important role.However, whether Shengu granules attenuate PMOP by modulating gut flora and related mechanisms remains unclear. In this study. We examined the bone strength of the femur, the structure of the intestinal microbiota and SCFAs in the feces, the level of FOXP3 cells in the colon, the condition of the mucosa, and the level of cytokines in the serum, the protein expression of OPG and RANKL in femur, the protein expression of ZO-1 and Occludin in colon. Our research has found that Shengu granules restored a significant amount of intestinal flora. Improvement of intestinal flora disorders, elevation of its metabolite SCFAs and elevation of the proportion of FOXP3 cells decreased the expression of serum IL-17 and TNF-α and increased the expression of serum IL-10 and TGF-β. On the one hand, it reduced intestinal inflammation and repaired the intestinal barrier; on the other hand, it regulated the OPG/RANKL signaling axis, thus thereby ameliorating bone loss.